2019
DOI: 10.3892/mmr.2019.10426
|View full text |Cite
|
Sign up to set email alerts
|

Urate transport capacity of glucose transporter 9 and urate transporter 1 in cartilage chondrocytes

Abstract: Chronic gouty arthritis, caused by a persistent increase in, and the deposition of, soluble uric acid (sUA), can induce pathological chondrocyte destruction; however, the effects of urate transport and intracellular sUA on chondrocyte functionality and viability are yet to be fully determined. Thus, the aim of the present study was to investigate the presence and functionality of a urate transport system in chondrocytes. The expression profiles of two primary urate reabsorptive transporters, glucose transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…In this way, we describe for, the first time, that human macrophages express URAT1, a transmembrane protein that had been only reported in endothelial cells, adipocytes, and cartilage chondrocytes [5]. Notably, we found that URAT1 expression in macrophages decreased as uric acid concentration increased, which might partially explain the fact that TNF-alpha, TLR4, and CD11c expression reached a saturation point, which in turn led to a decrease their protein levels.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In this way, we describe for, the first time, that human macrophages express URAT1, a transmembrane protein that had been only reported in endothelial cells, adipocytes, and cartilage chondrocytes [5]. Notably, we found that URAT1 expression in macrophages decreased as uric acid concentration increased, which might partially explain the fact that TNF-alpha, TLR4, and CD11c expression reached a saturation point, which in turn led to a decrease their protein levels.…”
Section: Discussionsupporting
confidence: 57%
“…In humans, monosodium urate-also referred to as uric acid-is the end-product of purine metabolism [1]. Uric acid is mainly excreted in urine and then reabsorbed in epithelial cells of the proximal convoluted tubule by urate transporters, such as the urate anion transporter 1 (URAT1), a transmembrane protein highly expressed in endothelial cells, adipocytes, and cartilage chondrocytes [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Tese fndings indicate the GG genotype was signifcantly associated with lower blood UA levels and a lower risk of T2DM compared with the other two genotypes. GLUT9 [20] was once classifed as a glucose and/or fructose transporter and, although its transport activity is very low, GLUT9 has a large efect on glucose metabolism [7,21,22]. GLUT9 is upregulated in the liver and kidney tissues of diabetic mice and afects glucoseinduced insulin secretion in pancreatic β cells [6,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…GLUT9 [ 20 ] was once classified as a glucose and/or fructose transporter and, although its transport activity is very low, GLUT9 has a large effect on glucose metabolism [ 7 , 21 , 22 ]. GLUT9 is upregulated in the liver and kidney tissues of diabetic mice and affects glucose-induced insulin secretion in pancreatic β cells [ 6 , 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation